Multiple Disguises for the Same Party: The Concepts of Morphogenesis and Phenotypic Variations in Cryptococcus neoformans† - Zaragoza, Oscar (Frontiers in Microbiology, 2011)
Although morphological transitions (such as hyphae and pseudohyphae formation) are a common feature among fungi, the encapsulated pathogenic yeast Cryptococcus neoformans is found during infection as blastoconidia. However, this fungus exhibits striking variations in cellular structure and size, which have important consequences during infection. This review will summarize the main aspects related with phenotypic and morphological variations in Cryptococcus neoformans, which can be divided in three classes. Two of them are related to changes in the capsule, while the third one involves changes in the whole cell. The three morphological and phenotypic variations in C. neoformans can be classified as: 1) changes in capsule structure, 2) changes in capsule size, and 3) changes in the total size of the cell, which can be achieved by the formation of cryptococcal giant/titan cells or micro-forms. These changes have profound consequences on the interaction with the host, involving survival, phagocytosis escape and immune evasion and dissemination. This article will summarize the main features of these changes, and highlight their importance during the interaction with the host and how they contribute to the development of the disease.